Kepemimpinan Humanistik Kepala Sekolah dalam Membangun Budaya Belajar Siswa Sekolah Dasar Pada Masa Pandemi Covid-19 - Fauzan, Fauzan; Nabilah, Bilqis Firyal (International Conference on Islamic Studies, 2020)
Abstract: The study aims to identify the application of humanistic leadership in building a culture of elementary school student learning in the midst of the outbreak of the Covid-19 pandemic. This study is a literature study to obtain information on how to build a learning culture of elementary school students during the Covid-19 pandemic, challenges to the learning culture of school students during the Covid-19 pandemic, and the application of the principal's humanistic leadership in building a culture of learning of elementary school students during the pandemic Covid-19. In this study found that the learning policy at home, strengthened the role of parents in assisting their children in developing a culture of learning, especially elementary school age children. Learning at home can take advantage of online classes by using google classroom, zoom, and podcasts by the teacher. Studying at home is certainly different from studying at school because children must adapt to different ways of learning. Therefore the role of parents is crucial in the development of a culture of learning at home. To build a culture of learning at home, principals can apply humanistic leadership, where fulfillment of the needs of children when they studied at school is the responsibility of teachers and principals, now turning to parents. Principals can apply humanistic leadership so that the 5 hierarchies of children's needs (physiological needs, safety needs, compassion and belonging needs, self-esteem needs, and self-actualization needs) are fuldilled during they study at home so that children continue to learn at home in the middle of the Covid-19 pandemic.